Editorial - Apivatthakakul, MD, Theerachai (Journal of Southeast Asian Orthopaedics, 2022)
The Thai Journal of Orthopaedic Surgery Volume 43 / Number 1-2 January-April 2019 is published in April 2019. This issue in your hand consists of several interesting articles. The first one is the periprosthetic joint infection which help the surgeon to determine the appropriated treatment options. The second and the third is the trauma subjects to compare the treatment method for hip fractures and femoral fractures. The fourth is the predictive factors for radiological outcome after surgical treatment of acetabulum fracture. Lastly, the uncommon periprosthetic joint infection. Our journal is making progress in a positive way with supporting from the RCOST committee and all RCOST members who submit their valuable work in Orthopaedic field to demonstrated the up to date knowledge and skill or basic knowledge of Administration system to improve national policy in treating Orthopaedic patients.